PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK SMK NEGERI 3 SIDRAP - Harnawati Hading; Purnamawati (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research is a quantitative study which was analyzed descriptively using regression analysis. This study aims to determine the effect of pedagogic competence and professional competence of teachers on the learning motivation of students at Vacational High School 3 Sidrap. Sampling technique using technique Purposive Sampling and research sample is learners at state high school 3 Sidrap as many as 47 people . Data collection techniques through observation, questionnaire (questionnaire) and documentation. The data analysis technique used is analysis descriptive . The research results show t the level of teacher pedagogical competence at Vacational High School 3 Sidrap shows 48.94% of teachers are in the medium category. The level of teacher professional competence shows that 68.09% of teachers are in the high category. The level of learning motivation of students is in the high category of 46.81%. The pedagogical competence and professional competence of teachers have an effect simultaneous on the learning motivation of students at SMK Negeri 3 Sidrap by 72.7%.